Factors influencing female consumers' purchase intention towards cosmetic products in online stores in China - Meng Wan, Ma (Kulliyyah of Economics and Management Sciences International Islamic University Malaysia, 2020)
In the past ten years, China's e-commerce has grown tenfold as fast and became the largest e-commerce market in the world. Meanwhile, cosmetics industry has also become a demand in e-commerce. Therefore, female consumers as the mainstream consumer of online shopping, and cosmetics become the focus and centre of shopping for them. Thus, there is a vast potential market for cosmetic industry in China due to the influence of the global economy because China is the largest e-commerce country and the second largest cosmetic market around the world. This has led to increased interest among researchers regarding the factors influencing female consumers' intention to buy cosmetic products in online stores in China. This study examines the factors that influence consumers' intention to buy cosmetic products in online stores in China and the conceptual model incorporates trust and price in the Theory of Planned Behaviour (TPB).Also, primary data was collected using purposive sampling by distributing a self-administrated questionnaire in China of which 384 were valid for analysis in four cities (Beijing, Shanghai, Chongqing and Yunnan), SPSS was also used to analyse the collected data and determine the constructs' reliability, Exploratory factor analysis (EFA) and multiple regression analysis were also performed. The results revealed that attitude, price and trust significantly and positively influence female consumers' intention to buy cosmetic products in online stores in China while subjective norm and perceived behavioural control do not have a significant influence on consumer's purchase intention to buy cosmetic online. Implications for marketers as well as suggestions for future research are discussed.